Impact of post‐kidney transplant parathyroidectomy on allograft function. (28th February 2013) - Parikh, Samir; Nagaraja, Haikady; Agarwal, Anil; Samavedi, Srinivas; Von, Jon; Nori, Uday; Andreoni, Kenneth; Pesavento, Todd; Singh, Neeraj
Abstract Background The impact of parathyroidectomy on allograft function in kidney transplant patients is unclear. Methods We conducted a retrospective, observational study of all kidney transplant recipients from 1988 to 2008 who underwent parathyroidectomy for uncontrolled hyperparathyroidism (n = 32). Post‐parathyroidectomy, changes in estimated glomerular filtration rate (eGFR) and graft loss were recorded. Cross‐sectional associations at baseline between eGFR and serum calcium, phosphate, and parathyroid hormone (PTH), and associations between their changes within subjects during the first two months post‐parathyroidectomy were assessed. Results Post‐parathyroidectomy, the mean eGFR declined from 51.19 mL/min/1.73 m2 at parathyroidectomy to 44.78 mL/min/1.73 m2 at two months (p < 0.0001). Subsequently, graft function improved, and by 12 months, mean eGFR recovered to 49.76 mL/min/1.73 m2 (p = 0.035). Decrease in serum PTH was accompanied by a decrease in eGFR (p = 0.0127) in the first two months post‐parathyroidectomy. Patients whose eGFR declined by ≥20% (group 1) in the first two months post‐parathyroidectomy were distinguished from the patients whose eGFR declined by <20% (group 2). The two groups were similar except that group 1 had a higher baseline mean serum PTH compared with group 2, although not significant (1046.7 ± 1034.2 vs. 476.6 ± 444.9, p = 0.14). In group 1, eGFR declined at an average rate of 32% (p < 0.0001) during the first month post‐parathyroidectomy compared with 7% (p = 0.1399) in group 2, and the difference between these two groups was significant (p = 0.0003). The graft function recovered in both groups by one yr. During median follow‐up of 66.00 ± 49.45 months, 6 (18%) patients lost their graft with a mean time to graft loss from parathyroidectomy of 37.2 ± 21.6 months. The causes of graft loss were rejection (n = 2), pyelonephritis (n = 1) and chronic allograft nephropathy (n = 3). No graft loss occurred during the first‐year post‐surgery. Conclusion Parathyroidectomy may lead to transient kidney allograft dysfunction with eventual recovery of graft function by 12 months post‐parathyroidectomy. Higher level of serum PTH pre‐parathyoidectomy is associated with a more profound decrease in eGFR post‐parathyroidectomy.